MODEL PENINGKATAN DISIPLIN KERJA DAN KINERJA SUMBER DAYA MANUSIA TENAGA PENDIDIK DI SEKOLAH DASAR ISLAM TERPADU MELALUI KEPEMIMPINAN DIGITAL DANBUDAYA ORGANISASI - Liswinda, Ultra; Faeni, Dewi Puspaningtyas (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
In the era of digital transformation, Islamic elementary schools (SDIT) face serious challenges: inconsistent discipline and disparities in teacher performance, which hinder the effectiveness of school management. This study aims to formulate a model for improving teacher discipline and performance by strengthening digital leadership and Islamic organizational culture. Data were obtained using a qualitative case study approach in one SDIT, through in-depth interviews, participant observation, and documentation analysis. The analysis shows that visionary and adaptive digital leadership—which encourages teachers to adopt technology and collaboration—plays a significant role in building a culture of discipline and collaboration. Furthermore, an organizational culture that emphasizes shared values, collegial support, and Islamic moral responsibility strengthens the implementation of disciplinary practices and improves teacher academic performance. The findings of this study produce an integrated conceptual model that combines: (1) the digital vision of school leaders, (2) the involvement of technology in communication and monitoring, and (3) strengthening an Islamic work culture. Consequently, this model can serve as a strategic framework for SDIT managers in designing human resource development policies, improving teacher digital literacy, and strengthening an adaptive work culture amidst the dynamics of the digital era.